2023
DOI: 10.1002/adfm.202300710
|View full text |Cite
|
Sign up to set email alerts
|

Double Cross‐Linked Biomimetic Hyaluronic Acid‐Based Hydrogels with Thermo‐Stimulated Self‐Contraction and Tissue Adhesiveness for Accelerating Post‐Wound Closure and Wound Healing

Abstract: When skin trauma occurs, rapid achievement of the post‐wound closure is required to prevent microbial invasion, inhibit scar formation and promote wound healing. To develop a wound dressing for accelerating post‐wound‐closure and wound healing, a thermo‐responsive and tissue‐adhesive hydrogel with interpenetrating polymer networks (IPN) is fabricated based on N‐dimethylbisacrylamide (NIPAM) and glutaraldehyde (GTA) cross‐linked hyaluronic acid (HA). Results not only confirm the thermo‐stimulated self‐contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 76 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…Figure B showed that the supernatant of all CuS@A NPs samples at different concentrations was transparent and clear. The hemolysis rate of CuS@A NPs was much lower than the recommended safety value (2%) of biological materials, according to the authoritative evaluation standard . All results demonstrated that the CuS-based samples have good cytocompatibility and blood compatibility.…”
Section: Resultsmentioning
confidence: 84%
“…Figure B showed that the supernatant of all CuS@A NPs samples at different concentrations was transparent and clear. The hemolysis rate of CuS@A NPs was much lower than the recommended safety value (2%) of biological materials, according to the authoritative evaluation standard . All results demonstrated that the CuS-based samples have good cytocompatibility and blood compatibility.…”
Section: Resultsmentioning
confidence: 84%
“…Because of their direct exposure to the external environment, wounds are highly susceptible to microbial infections. Once a wound is infected, live bacteria secrete large volumes of toxic components that damage the surrounding healthy skin and can cause systemic poisoning or death. , To date, loading traditional antibacterial agents is the most common and effective method to endow hydrogels with antibacterial activity, thus resisting wound infections. Unfortunately, traditional antibacterial agents not only exhibit sustained cytotoxicity that can inhibit wound repair but also induce bacterial resistance, making appropriate treatment all the more difficult. Near-infrared (NIR) photothermal sterilization, which relies on NIR photosensitizers to convert NIR laser energy into heat to kill bacteria, offers several virtues, including its precision, wide antibacterial spectrum, and minimal side effects, consequently receiving widespread attention in recent years. Moreover, because it does not use toxic antibacterial agents nor has a specific target, NIR photothermal sterilization does not cause sustained cytotoxicity or lead to bacterial resistance. , As natural NIR photosensitizers, polydopamine nanoparticles (PDA-NPs) exhibit good NIR photothermal properties and excellent biocompatibility and are widely used in NIR photothermal sterilization and antitumor therapies. …”
Section: Introductionmentioning
confidence: 99%
“…(1) A system that creates mechanical interlocks and physical entanglements with the tissue surface; these materials are often cross-linked by free radical polymerization. , (2) The formational of covalent bonds between adhesive and tissue, through modification of the adhesive with a chemical binding site, wherein catechol and aldehyde modifications are the most prevalent methods. ,, However, catechol functionality is susceptible to oxidation, which poses challenges to adhesive performance . Recently, biopolymer-based hydrogels with aldehyde modification have been successfully developed and demonstrated excellent adhesive performance. Sigen et al designed an adhesive and injectable hydrogel composed of aldehyde-modified HA and a disulfide cross-linker 3,3′-dithiobis (propionic hydrazide) (DTPH), which showed excellent adhesive capabilities by outperforming bovine serum albumin-glutaraldehyde (BSAG) glue by 65.8% during a lap-shear study with enhanced biocompatibility . However, the use of aldehyde-modified biopolymers for enhanced adhesive properties often leads to a conflict between injectability and stability .…”
Section: Introductionmentioning
confidence: 99%